Living the confidence code - Kay, Katty; Shipman, Claire, 1962-; Riley, JillEllyn (Harper, 2020)
Profiles thirty girls from around the world who built confidence through taking on causes that were important to them. Through essays, photographs, and question-and-answer formats, describes the difficulties and failures each girl faced and how they overcame stumbling blocks to help others and themselves.